High anxiety levels associated with elevated blood glucose in older adults with type 2 diabetes: An Indonesian sample - Arman, Mohammed; Wantonoro, Wantonoro (Universitas Aisyah Pringsewu, 2024)
Background: Aging is a gradual and irreversible pathophysiological process. Being older increased health problems both physically and mentally such as glucose and anxiety level. Aim: to analyze the correlation between anxiety levels and glucose older person. Methods: a quantitative correlational research design. Anxiety was assessed with HARS questionnaire, while glucose was determined through face-to-face monitoring. Pearson correlation statistical analysis was used to examine the correlation between anxiety and glucose. Results: Fifty older persons with diabetic diagnose were included in this study. Pearson correlations test showed that there was significant correlation between anxiety and glucose levels in older persons confirmed (?=0.001). Conclusion: Higher anxiety was associated with increased blood glucose among older adult with diabetic Type-II. Therefore, intervention program for anxiety in older persons with diabetic are needed in order to manage glucose levels. Investigate specific nursing intervention strategy for older persons with diabetic are recommended for future study. Abstrak: Latar Belakang: Penuaan adalah proses patofisiologis yang terjadi secara bertahap dan tidak dapat dihindari. Menjadi lebih tua meningkatkan masalah kesehatan baik secara fisik maupun mental, seperti kadar glukosa dan tingkat kecemasan. Tujuan: Menganalisis hubungan antara tingkat kecemasan dan kadar glukosa pada lansia. Metode: Penelitian kuantitatif dengan desain korelasional. Kecemasan dinilai menggunakan kuesioner HARS, sedangkan kadar glukosa ditentukan melalui pemantauan langsung. Analisis statistik korelasi Pearson digunakan untuk menguji hubungan antara kecemasan dan kadar glukosa. Hasil: Lima puluh lansia dengan diagnosis diabetes diikutsertakan dalam penelitian ini. Uji korelasi Pearson menunjukkan adanya hubungan yang signifikan antara tingkat kecemasan dan kadar glukosa pada lansia (?=0.001). Kesimpulan: Tingkat kecemasan yang lebih tinggi berhubungan dengan peningkatan kadar glukosa darah pada lansia dengan diabetes tipe II. Oleh karena itu, program intervensi untuk mengatasi kecemasan pada lansia dengan diabetes diperlukan guna mengelola kadar glukosa. Penelitian lebih lanjut disarankan untuk mengeksplorasi strategi intervensi keperawatan yang spesifik bagi lansia dengan diabetes.